2014
DOI: 10.1002/jcp.24641
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating Agent 5‐Aza‐2′‐deoxycytidine (DAC) Ameliorates Multiple Sclerosis in Mouse Models

Abstract: Increasing evidence supports the role of epigenetics in the development of autoimmune disorders and the possibility of using epigenetic modifying drugs in the context of MS has not yet been investigated. We have explored the effect of the hypomethylating agent 5-aza-2'-deoxycytidine (DAC) in two murine models of experimental allergic encephalomyelitis (EAE). DAC treatment was associated with a significant amelioration of the clinical and histological hallmarks of EAE in both models. These effects were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Studies show that prophylactic and therapeutic treatment of mice with the DNA hypomethylating agent, decitabine (5′-aza-2′-deoxycytidine, DAC) suppressed disease severity in experimental autoimmune encephalomyelitis (EAE) [63,64]. DAC reduced CNS inflammatory cytokines and lymphocyte infiltration while increasing anti-inflammatory cytokines.…”
Section: Epigenetic Evidence Of Altered Dna Methylation In Cns and Pementioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that prophylactic and therapeutic treatment of mice with the DNA hypomethylating agent, decitabine (5′-aza-2′-deoxycytidine, DAC) suppressed disease severity in experimental autoimmune encephalomyelitis (EAE) [63,64]. DAC reduced CNS inflammatory cytokines and lymphocyte infiltration while increasing anti-inflammatory cytokines.…”
Section: Epigenetic Evidence Of Altered Dna Methylation In Cns and Pementioning
confidence: 99%
“…Therefore, DAC may have opposing immunoregulatory and immunogenic effects. Indeed, increased myelin-specific Th cell proliferation was observed in DAC-treated EAE mice [63], which could perpetuate or enhance CNS immune attack. Additionally, an early study showed that rats treated with DNA methylation inhibitor 5-azacitidine (5-AZA) presented reduced myelin levels and altered action potential formation in the optic nerve [67].…”
Section: Epigenetic Evidence Of Altered Dna Methylation In Cns and Pementioning
confidence: 99%
“…CTAs frequently have cancer-restricted expression, regardless of tumor type, to prevent autoimmune reactions to normal tissues [102]. In fact, decitabine not only prevents autoimmune response in tumor patients, but also increases the function of Treg, which inhibits the function of effector T cells, to ameliorate multiple sclerosis [103] or inhibit cardiac allograft [104] in mouse model, when decitabine used alone or combined with IL-35, respectively. Previous report has demonstrated that decitabine stably induces FOXP3 expression in CD4 + T cells and converts CD4 + T cells into Treg [105].…”
Section: Combination Of Immunotherapy and Decitabinementioning
confidence: 98%
“…Decitabine (5-aza-2′-deoxicytidine), which is a DNMT inhibitor, induces Foxp3 expression in mice exposed to experimental autoimmune encephalomyelitis (EAE, a MS murine model) by demethylating CpG islands in the gene encoding Foxp3. As a result, this drug decreases spinal infiltration and ameliorates disease progression [97]. A crosstalk has been described between DNA methylation and histone acetylation.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…A crosstalk has been described between DNA methylation and histone acetylation. For example, MeCP2, a reader of methylated DNA, suppresses the brain neurotrophic factor expression, which is necessary for myelin repair, whereas histone acetyltransferase expression and HDAC inhibitors reduce MeCP2 expression and thus favor remyelination [97].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%